Smart Medical System for the Universal Remote Delivery of Rehabilitation. (2013) - Epelde, Gorka; Carrasco, Eduardo; Rajasekharan, Shabs; Abascal, Julio; Jimenez, Jose Manuel; Vivanco, Karmelo; Gomez-Fraga, Isaac; Valencia, Xabier
No abstract available